2021
DOI: 10.1016/j.annonc.2021.10.125
|View full text |Cite
|
Sign up to set email alerts
|

107P The evolving diagnostic and treatment landscape in metastatic non-small cell lung cancer (mNSCLC) across Europe: A real world evidence survey

Abstract: platinum choice, chemotherapy cycles and PCI or thoracic radiotherapy use. PD-L1 (atezolizumab or durvalumab) plus chemotherapy showed an improvement in median rwPFS. Further analysis in overall survival is still needed to explore the benefit and characteristic factors that may influence the PD-L1 use in Chinese ES-SCLC patients.Legal entity responsible for the study: The authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In spite of increasing progress in the development of targeted therapeutics and immunotherapeutic strategies, chemotherapy remains a major first-line treatment option for advanced NSCLC in European countries so far. 7,8,65 A gold standard chemotherapy for NSCLC includes a platinum-based doublet, a combination of cisplatin (or carboplatin) with another cytostatic drug such as pemetrexed, gemcitabine, etoposide, or paclitaxel. Although tumor responsiveness to chemotherapeutics is highly variable and chemotherapy usually holds a high risk of adverse effects, there are no reliable genetic biomarkers to predict its efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of increasing progress in the development of targeted therapeutics and immunotherapeutic strategies, chemotherapy remains a major first-line treatment option for advanced NSCLC in European countries so far. 7,8,65 A gold standard chemotherapy for NSCLC includes a platinum-based doublet, a combination of cisplatin (or carboplatin) with another cytostatic drug such as pemetrexed, gemcitabine, etoposide, or paclitaxel. Although tumor responsiveness to chemotherapeutics is highly variable and chemotherapy usually holds a high risk of adverse effects, there are no reliable genetic biomarkers to predict its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although genomics and transcriptomics technologies have opened an avenue for precision medicine by linking genetic alterations and upregulated signaling pathways to targeted drugs, 3,4 there are no reliable biomarkers for prediction of tumor responses to chemotherapy, 5,6 which remains a major treatment option for advanced NSCLC. 7,8 Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Pandemic-related delays and changes in cancer diagnosis, treatment and follow-up, along with social distancing, may have added new sources of stress and anxiety for many patients. 2,4,[8][9][10] Psychological symptoms such as depression together with physical symptoms such as weight loss at the time of lung cancer diagnosis are prognostically relevant and predict worse survival. 11,12 While there are some studies on the impact of the COVID-19 pandemic on patient-reported outcomes (PROs) in lung cancer, those analyses either included rather small patient cohorts, 4,[13][14][15] more selective patients from randomised controlled clinical trials (RCTs) 12 or assessed PROs only at one time point.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with lung cancer under treatment have been associated with a high risk of SARS‐CoV‐2 infection and potentially worse outcome 6,7 . Pandemic‐related delays and changes in cancer diagnosis, treatment and follow‐up, along with social distancing, may have added new sources of stress and anxiety for many patients 2,4,8–10 . Psychological symptoms such as depression together with physical symptoms such as weight loss at the time of lung cancer diagnosis are prognostically relevant and predict worse survival 11,12 .…”
Section: Introductionmentioning
confidence: 99%